2019
DOI: 10.20897/jcasc/6358
|View full text |Cite
|
Sign up to set email alerts
|

‘You won’t See Anyone Promoting a Bronze’: Awards and Ambivalence Amongst Craft Gin Producers

Abstract: The recent surge in the popularity of 'craft' and 'artisanal' spirits made in small batches by independent producers raises a range of questions about the processes by which the economic and cultural value of consumer products and practices are assessed and acknowledged. Drawing on qualitative interviews with 20 craft gin distillery workers in the UK, this paper analyses the role played by trade and press awards in this process. Whilst the majority of interviewees had received awards for their products and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A number of factors influence the lack of women entering the craft drinks sector. Studies of craft brewers (Miller, 2019; Thurnell‐Read, 2014) and craft distillers (Ocejo, 2017; Thurnell‐Read, 2019b) have shown that many enter the trade having left previous white‐collar, and often well‐paid, jobs. Craft spirits producers who progress through initially amateurish explorations to increasingly professional distilling operations do so by drawing on their economic and cultural capital accrued in previous white‐collar professions (Ocejo, 2017).…”
Section: Gender At Work In the Craft Drinks Sectormentioning
confidence: 99%
“…A number of factors influence the lack of women entering the craft drinks sector. Studies of craft brewers (Miller, 2019; Thurnell‐Read, 2014) and craft distillers (Ocejo, 2017; Thurnell‐Read, 2019b) have shown that many enter the trade having left previous white‐collar, and often well‐paid, jobs. Craft spirits producers who progress through initially amateurish explorations to increasingly professional distilling operations do so by drawing on their economic and cultural capital accrued in previous white‐collar professions (Ocejo, 2017).…”
Section: Gender At Work In the Craft Drinks Sectormentioning
confidence: 99%